2018
DOI: 10.1039/c8mt00161h
|View full text |Cite
|
Sign up to set email alerts
|

The type 4 metallothionein from Brassica napus seeds folds in a metal-dependent fashion and favours zinc over other metals

Abstract: The problem of handling zinc in the cell is of great importance because zinc is an indispensable micronutrient involved in most physiological processes in all living organisms. Moreover, our understanding of mechanisms governing the discrimination between micronutrients and toxic metals on the level of individual proteins to the whole-organism level is incomplete. Metallothioneins are able to bind heavy metal ions, and roles in zinc homeostasis have been proposed. Here, we have studied the in vitro and in vivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 86 publications
0
10
0
Order By: Relevance
“…Kagi and Vallee reported one of the earliest attempts to isolate MT from equine renal cortex, and Kagi and co-workers have reported important applications of both NMR ,, and MS for studies of structure of Cd 7 -MT and cooperativity of metalation. Lobinski and co-workers used both microscale purification techniques (HPLC, capillary electrochromatography) and trace analysis techniques, including ESI-MS, to successfully detect MT isoforms from different systems. Atrian, Capdevila, and co-workers used ESI-MS to investigate metal binding of MT from different species and to bridge the gap between phytochelatins and metallothions. Stillman and co-workers have made extensive use of ESI-MS for studies of ion reactivity and kinetics in metalation reactions of MT employing a broad range of metal ions. Blindauer and co-workers have reported MT expression in different species and dynamics of metal binding and release employing multiple analytical methods including MS. …”
mentioning
confidence: 99%
“…Kagi and Vallee reported one of the earliest attempts to isolate MT from equine renal cortex, and Kagi and co-workers have reported important applications of both NMR ,, and MS for studies of structure of Cd 7 -MT and cooperativity of metalation. Lobinski and co-workers used both microscale purification techniques (HPLC, capillary electrochromatography) and trace analysis techniques, including ESI-MS, to successfully detect MT isoforms from different systems. Atrian, Capdevila, and co-workers used ESI-MS to investigate metal binding of MT from different species and to bridge the gap between phytochelatins and metallothions. Stillman and co-workers have made extensive use of ESI-MS for studies of ion reactivity and kinetics in metalation reactions of MT employing a broad range of metal ions. Blindauer and co-workers have reported MT expression in different species and dynamics of metal binding and release employing multiple analytical methods including MS. …”
mentioning
confidence: 99%
“…It has been only shown that the overexpression of NnMT2a and NnMT3 in Arabidopsis improves seed vigour under oxidative stress (Zhou et al., ). We demonstrated recently that BnMT4 expression is also modulated by metal ions during seed germination (Mierek‐Adamska, Dąbrowska, & Blindauer, ). An increase in mRNA level of AtMT4b but not AtMT4a in response to hydrogen peroxide was annotated but during seed development (Ren et al., ).…”
Section: Resultsmentioning
confidence: 95%
“…In relation to this, we speculate that the participation of antioxidant scavengers in triggering these transduction events needs further elucidation. Besides these antioxidant enzymes, participation of a metal binding protein metallothionein (MT) as an H 2 O 2 scavenger has also been reported (Zhou et al, 2012;Leszczyszyn et al, 2013;Mierekadamska et al, 2018). Expression of two metellothinein genes MT1 and MT4 were found be highly induced in nanoprimed tomato seeds, suggesting their possible involvement in ROS signaling during germination of nanoprimed seeds (Anand et al, 2019).…”
Section: Role Of Antioxidant Scavenging System In Promoting Germinatimentioning
confidence: 98%